2021
DOI: 10.1080/21645515.2020.1844505
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the burden of pertussis in South Korea

Abstract: This review summarizes the published data on epidemiology and burden of pertussis in South Korea as these may be under-categorized. A systematic literature review of PubMed, SCOPUS, EMBASE and KMBASE was performed to identify published literature in South Korea since 2000. Pertussis detection rates among 19 eligible studies range from 0.7% to 100% across different age groups, detection methods and study settings. Highest rates are observed in infants, while adolescents and adults with pertussis infection may s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Pertussis is a highly contagious respiratory infection; although universal vaccination substantially reduced the numbers of cases and deaths, epidemic cycles occur every two to five years, even in countries with high vaccination coverage. 2 5 Studies have demonstrated that the protection induced by immunization wanes rapidly, being effective for only 2–3 years. 29 Many countries recommend Tdap administration in those aged 11–12 years and a decennial booster dose of Td or Tdap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pertussis is a highly contagious respiratory infection; although universal vaccination substantially reduced the numbers of cases and deaths, epidemic cycles occur every two to five years, even in countries with high vaccination coverage. 2 5 Studies have demonstrated that the protection induced by immunization wanes rapidly, being effective for only 2–3 years. 29 Many countries recommend Tdap administration in those aged 11–12 years and a decennial booster dose of Td or Tdap.…”
Section: Discussionmentioning
confidence: 99%
“…Diphtheria, tetanus, and pertussis are community-acquired infectious diseases that can be life-threatening. 1 2 Despite the substantial decline in incidence of diphtheria and tetanus and their near elimination due to immunization in developed countries, these diseases remain endemic in some developing countries with low vaccination coverage. Outbreaks of diphtheria are reported continuously in regions that are predominantly rural or in a state of economic crisis or civil war.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tdap for pregnant women and adults in contact with neonates has been recommended since 2017 [ 83 ]. A single dose of Tdap is also recommended for adults, with a booster dose every 10 years [ 84 ].…”
Section: East Asiamentioning
confidence: 99%
“…In general, people are vulnerable to infection, but children are more susceptible. After decades of a consistently low incidence of scarlet fever and pertussis, a dramatic increase has been seen in many countries in recent years, such as the United Kingdom [ 1 , 2 ], China [ 3 , 4 ], and Korea [ 5 , 6 ]. Scarlet fever is an acute respiratory infection that develops in some people who have strep throat.…”
Section: Introductionmentioning
confidence: 99%